THE EFFECT OF ATMOSPHERICS ON BEHAVIORAL INTENTION AT KOREAN RESTAURANT IN SURABAYA - Riyantyari Hayu Prameswari; Christina R. Honantha; Indri Hapsari (CALYPTRA, 2018)
Abstract – This study aims to observe the influences of atmospherics on behavioral intention, both directly and mediated through quality perception. Korean restaurant is used an object for ethnic restaurant observed in this study.A quantitative and causal type research is adopted for this study. Questionnaire used was adopted from Ha and Jang (2012) for offline survey. Purposive sampling method was used in this study. Sample consisted of 160 respondents, whose age is 18 years old or above and have eaten in Korean restaurant in Surabaya for at least three times in the past six months. Further data analysis was analyzed by SPSS 22.0 and AMOS 22.0.Result of this study found positive relationship between atmospherics on service quality. Atmospherics also positively influences food quality. Positive relationship was also found on the relationship of service quality on behavioral intention. Moreover, food quality also positively influences behavioral intention. Service quality was proven as mediator in the influences of atmospherics on behavioral intention. Additionally, food quality was also proven as mediator in the influences of atmospherics on behavioral intention. However, this study found atmospherics has no impact on behavioral intention.